Estratégia de operações e gestão ambiental: estudo multi-casos em empresas industriais certificadas ISO-14001 - Ribeiro, José Roberto Soares (Universidade Federal de São Carlos, 2018)
The aim of this doctoral thesis was to verify if the environment could be considered in the Operations Strategy (OS) as a new competitive priority of the Operations, together with Cost, Delivery, Flexibility and Quality. For this, it was analyzed how the Environmental Management (EM) and the OS are related in ISO-14001 certified industrial companies. Data were collected through bibliographic research, semi-structured interviews, systematic observations and documentary consultation. It was a research with a qualitative approach using the case study technique in the companies Natura Cosméticos S/A, Tilibra Produtos de Papelaria Ltda. and companies X and Y. The results pointed out that the environment can be considered in the OS a new competitive priority of Operations, thus constituting a factor of competitive differentiation, but in conjunction with Innovation and Sustainability or Triple Bottom Line. EM, on the other hand, constitutes an infra-structural decision area of the OS, being able to base the Competitive Strategies (CS) of differentiation or of low cost. That is, the company can work the environment as a factor of competitive differentiation or only of qualification next to the consumer market, being able to extrapolate the objective of complying with the legislation or corporate guidelines. In any case, the environment may be in the Mission, Vision and Values of the company and its OS, having the potential for competitive differentiation, for to leverage of the company in your market, also for to reduce cost through continuous improvement projects involving consumptions of imputs, such water and energy.
Keywords: Estratégia de Operações; Gestão ambiental; Sustentabilidade; Triple Bottom Line; Estratégia Competitiva; Operations strategy; Environmental management; Sustainability; Triple Bottom Line; Competitive strategy; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO DA PRODUCAO; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO; ENGENHARIAS::ENGENHARIA DE PRODUCAO